Perceptions About Verbal Aggression: Survey of Secondary Students With Emotional and Behavioral Disorders. (March 2023) - Poling, Daniel V.; Smith, Stephen W.
Researchers have found that verbal aggression (VA) is the most frequent form of aggression reported in U.S. schools across all grade levels. There are numerous harmful outcomes for VA perpetrators, victims, and witnesses including depression, anxiety, decreased academic performance, and low sense of school belonging. Moreover, VA is known to occasion physically aggressive responses, making VA especially problematic for students who exhibit chronic maladaptive behavior profiles. In this study, therefore, we surveyed 144 middle and high school students identified with an emotional and behavioral disorder to understand their involvement with VA, response to victimization, and what VA messages lead to physical aggression. We also investigated the locations of VA incidents, student perceptions about teacher-delivered consequences for VA, and witness behavior. We discuss the implications for practice, including explicit skill instruction for students and incorporating content about VA into preservice teacher coursework covering prevention and intervention strategies. Finally, we provide suggestions for future research such as conducting observations across a variety of school settings and in different regions of the country, and collecting qualitative data to enrich quantitative findings.